2013
DOI: 10.5751/es-05694-180239
|View full text |Cite
|
Sign up to set email alerts
|

Equity and REDD+ in the Media: a Comparative Analysis of Policy Discourses

Abstract: ABSTRACT. Reducing emissions from deforestation and forest degradation (REDD+) is primarily a market-based mechanism for achieving the effective reduction of carbon emissions from forests. Increasingly, however, concerns are being raised about the implications of REDD+ for equity, including the importance of equity for achieving effective carbon emission reductions from forests. Equity is a multifaceted concept that is understood differently by different actors and at different scales, and public discourse hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 39 publications
0
56
0
1
Order By: Relevance
“…Having declared its commitment, the country has taken steps to reduce deforestation, despite controversy over the new forestry law, which opponents fear will reinforce the power of large-scale businesses, such as soybean farms and cattle ranching, that drive deforestation (Stickler et al 2013). Land tenure issues are openly discussed, and equity considerations are prominent in REDD+ policy debates because of the presence of well-established environmental justice nongovernmental organizations (NGOs) concerned mainly with indigenous peoples' rights (May et al 2011b, Di Gregorio et al 2013, Gebara et al 2014). …”
Section: Redd+ In Domestic Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having declared its commitment, the country has taken steps to reduce deforestation, despite controversy over the new forestry law, which opponents fear will reinforce the power of large-scale businesses, such as soybean farms and cattle ranching, that drive deforestation (Stickler et al 2013). Land tenure issues are openly discussed, and equity considerations are prominent in REDD+ policy debates because of the presence of well-established environmental justice nongovernmental organizations (NGOs) concerned mainly with indigenous peoples' rights (May et al 2011b, Di Gregorio et al 2013, Gebara et al 2014). …”
Section: Redd+ In Domestic Contextsmentioning
confidence: 99%
“…In addition, economic development is a high national priority, with related issues including demands by local governments to have the right to convert forest for development purposes and the launch of a new multibillion-dollar national development program known as MP3EI (Economic Masterplan 2011-2025, which overlaps with potential REDD+ areas (Indrarto et al 2012, Moeliono et al 2014. Civil society actors also are engaged in the REDD+ arena, where they are challenging Ecology and Society 19(4): 14 http://www.ecologyandsociety.org/vol19/iss4/art14/ the state mainly on issues of environmental justice and equity, such as tenure and indigenous rights (Di Gregorio et al 2013). …”
Section: Redd+ In Domestic Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three plausible explanations for the limited media coverage of REDD+ and avoidance of domestic policy issues. First, REDD+ is partly seen as lying within the framework of international climate justice, which pays limited attention to national/local politics (Di Gregorio et al 2013). Second, REDD+ is not yet fully implemented and there is little understanding of many of the operational issues, such as mechanisms for MRV, setting reference levels, REDD+ implementation framework and benefit-sharing mechanisms.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…government agencies and donors) with limited participation of vulnerable and marginalized groups (e.g. customary users, indigenous groups) (Babon and Gowae 2013; Che Piu and Menton 2013;Indrarto et al 2012;Di Gregorio et al 2013;Dkamela 2011;Jagger et al 2012;Mpoyi et al 2013;Müller et al 2014;Paudel et al 2013). In Vietnam, Pham et al (2014) identified a dominant role of government agencies in REDD+ policy making, and limited political space for non-state actors (e.g.…”
Section: Redd+mentioning
confidence: 99%